TINGKAT KELANGSUNGAN HIDUP BENIH IKAN BETOK (A.TESTUDINEUS, BLOCH) YANG DIPELIHARA DIDALAM WADAH YANG MENGGUNAKAN SHELTER BAMBU, PARALON DAN TEMPURUNG KELAPA - M Yusuf Arifin; Muhammad Sugihartono; Agusten Roy Marpaung (Universitas Batangahari Jambi, 2020)
Betok fish is very popular with the people because of the delicious and tasty taste of the meat, therefore this type of fish is quite potential for cultivation. (Muslim 2008) in (Anggara et al 2013). Most people who cultivate betok fish (A.testudineus, Bloch) do not understand their character or behavior, so that many farmers experience complaints in maintenance, especially in their growth and survival. As an alternative to the maintenance of Betok fish (A. testudineus, Bloch), the growth rates and viability of the Betok (A. testudineus, Bloch) fry were reared in a container using a shellter. The research design used was an environmental design RAL (completely randomized design) consisting of 4 (four) treatments and 3 (three) replications. The treatments were as follows: Treatment A: Betok fish seeds (A. testudineus, Bloch) without treatment (control), Treatment B: Betok fish seeds (A. testudineus, Bloch) were given a bamboo shellter ,, Treatment C; Betok fish (A. testudineusBloch) was given a coconut shell shellter, Treatment D: Betok fish (A.testudineusBloch) was given a paralon shellter. The results showed that betok (A. tetstudineus, Bloch) seeds were maintained using a shelter (Treatment C and B) resulted in better survival rates (99.35% & 98.07%) than treatments A and D (96.15% & 96.79%).